A generalised commodity theory of exploitation - Photis Lysandrou (City, University of London, City Political Economy Research Centre (CITYPERC), 2024)
This paper argues that the conceptual framework of Marx's Capital allows for the extraction of a commodity-based theory of capitalist exploitation that is distinct from the traditional labour-value based theory. The rationale for extracting such a theory is that it allows for an explanation of the current rise in global economic inequality in a way that shows this development to be entirely consistent with the fundamental laws of capitalism as it enters its globalised and financialised stage of development.
Keywords: 330; commodity; capitalist exploitation; globalised capitalism; financialised capitalism